2020
DOI: 10.1101/2020.02.05.20019653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence that Telomere Length is Causal for Idiopathic Pulmonary Fibrosis but not Chronic Obstructive Pulmonary Disease: A Mendelian Randomisation Study

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease accounting for 1% of UK deaths. In the familial form of pulmonary fibrosis, causal genes have been identified in ~30% of cases, and a majority relate to telomere maintenance. Prematurely shortened leukocyte telomere length has also been associated with IPF, as well as chronic obstructive pulmonary disease (COPD), a disease with a similar demographic and shared risk factors. Using Mendelian randomisation (MR), our study aimed to determine w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Recent evidence also supports a causal role for prematurely short telomeres in idiopathic PF. One study showed very short telomere lengths, similar in length to those found in patients with familial PF, in biopsies from the lungs of 15 of 28 IPF patients (10) and our team reported results inferring a causal effect of short telomeres in IPF using the statistical method of Mendelian randomization in large cohorts with genetic data (11). Studies in mouse models have shown that it is the AEC2 that are key to the short telomeric cause of lung remodeling and fibrosis (98) with dysfunctional chromosomal replication leading to cellular senescence and triggering the pro-fibrotic senescence-associated secretory phenotype (SASP) (99).…”
Section: Ageing Telomere Attrition and Cellular Senescencesupporting
confidence: 58%
See 2 more Smart Citations
“…Recent evidence also supports a causal role for prematurely short telomeres in idiopathic PF. One study showed very short telomere lengths, similar in length to those found in patients with familial PF, in biopsies from the lungs of 15 of 28 IPF patients (10) and our team reported results inferring a causal effect of short telomeres in IPF using the statistical method of Mendelian randomization in large cohorts with genetic data (11). Studies in mouse models have shown that it is the AEC2 that are key to the short telomeric cause of lung remodeling and fibrosis (98) with dysfunctional chromosomal replication leading to cellular senescence and triggering the pro-fibrotic senescence-associated secretory phenotype (SASP) (99).…”
Section: Ageing Telomere Attrition and Cellular Senescencesupporting
confidence: 58%
“…Animal studies clearly show that herpes virus-associated changes occur prior to onset of clinical features and in some cases that early treatment provides more greater benefit than later (81). For this reason, it will be all the more important to identify and diagnose people in the early stages of PF and to conduct trials at this time, rather than at symptomatic presentation, which is likely to represent a more treatment-resistant "end-stage" situation (11,121,122).…”
Section: Diagnosis Of Significant Herpes Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, recipient telomere length has consistently been shown to alter post-transplant outcomes, particularly in those with very short telomeres (20). A significant proportion of idiopathic pulmonary fibrosis is attributable to telomere related gene mutations (21)(22)(23)(24). Patients with pulmonary fibrosis related to such mutations, with extreme telomere shortening, may be more prevalent in the transplant population, owing to their earlier age of onset and worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a role for telomere dysfunction in driving PF, AT2 cells in sporadic PF express hallmarks of senescence and have shorter telomeres in fibrotic regions than those in non-fibrotic regions (Disayabutr et al, 2016;Kropski et al, 2015;Snetselaar et al, 2017). Additionally, two human Mendelian randomization studies argue that short telomeres are a cause of PF (Duckworth et al, 2020;Telomeres Mendelian Randomization Collaboration et al, 2017). Murine studies also argue that telomere dysfunction and senescence in AT2 cells can drive PF (Naikawadi et al, 2016;Povedano et al, 2015;Yao et al, 2020).…”
Section: Introductionmentioning
confidence: 92%